La tecnología en las relaciones CTS. Una aproximación al tema - Acevedo Díaz, José Antonio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
The aim of this paper is to revalue the technology in STS perspective. First, being based on Kline’s typology and Pacey’s conceptual model, several meanings of the technology are described. Second, the technological literary meaning is focused on the citizen training to participate in the democratic process of the sociotechnological decision making. Finally, after a review of the principal results obtained in the students’ and teachers’ beliefs research about the nature of technology and science, and their interactions within society, we tentatively make a STS proposal for the technology education in the compulsory secondary school.